Field development of Posidonia oceanica seedlings changes under predicted acidification conditions. (April 2023) - Pansini, Arianna; Beca-Carretero, Pedro; Berlino, Manuel; Sarà, Gianluca; Stengel, Dagmar B.; Stipcich, Patrizia; Ceccherelli, Giulia
Abstract: Ocean acidification has been consistently evidenced to have profound and lasting impacts on marine species. Observations have shown seagrasses to be highly susceptible to future increased p CO2 conditions, but the responses of early life stages as seedlings are poorly understood. This study aimed at evaluating how projected Mediterranean Sea acidification affects the survival, morphological and biochemical development of Posidonia oceanica seedlings through a long-term field experiment along a natural low pH gradient. Future ocean conditions seem to constrain the morphological development of seedlings. However, high p CO2 exposures caused an initial increase in the degree of saturation of fatty acids in leaves and then improved the fatty acid adjustment increasing unsaturation levels in leaves (but not in seeds), suggesting a nutritional compound translocation. Results also suggested a P. oceanica structural components remodelling which may counteract the effects of ocean acidification but would not enhance seagrass seedling productivity. Highlights: Development of Posidonia oceanica seedlings was investigated in field predicted OA. OA limits the stimulation of P. oceanica early life stage morphological development. FA remodelling improves the seedling resilience to prolonged exposures of low sea pH. Increased CO2 availability would not enhance seagrass seedling productivity.